Model Kolaboratif Penanggulangan Kemiskinan Ekstrem melalui Konsep Hexahelix di Provinsi Papua Barat Daya - Ibal, La; Madaul, Rahful A.; Rifqah, Nabila Nur (JURNAL SOSIAL HUMANIORA (JSH), 2023)
Southwest Papua Province, part of Indonesia, faces significant developmental challenges, especially extreme poverty influenced by its adherence to customary law. With a poverty rate of 14.2 percent, this research employs problem-solving methods like qualitative and descriptive approaches. The study reveals a collaborative approach to combat extreme poverty in the region, involving various stakeholders and supported by additional contributors. This coalition includes regional authorities, academics, businesses, private individuals, media, communities, and traditional institutions. Further support comes from banks, NGOs, markets, local industries, and small-scale entrepreneurs. Each party has a distinct role: the government oversees, academics provide frameworks, businesses support, communities drive progress, media spreads information, and traditional institutions plan interventions. This multi-stakeholder strategy is crucial in addressing extreme poverty in Southwest Papua Province, harnessing diverse roles for sustainable change.